The digital economy in Algeria-opportunities and prospects- Economie numérique en Algérie - opportunités et perspectives – - Messiliti, Nabila; Benzaama , Salima; Hadj , e (Finance and Business Economies Review, 2023)
Algeria treid to develop the information and communication technology through various actions, as to establish sectoral policy of the post and wired and wireless communications sice the beginning oft he year 2000. Creating a legal environment conducive to competition and improve access to telecommunications services, especially mobile phone service. In 2008, Algeria develops a real strategy clear and consistent to support the digital transformation in the Algerian economy. But the project e- Algeria was abandoned in the middle oft he road. Even today, the Algerian cannot, buy, sell, reserve through the internet. Experts explained this situation in the absence of political will to develop the digital economy in Algeria. But the collapse of oil prices has forced Algeria to diversify the economy on the basis of ICT and the knowledge economy.